Search 75,713 tutors
FIND TUTORS
Ask a question
0 0

Factoring?

Tutors, please sign in to answer this question.

2 Answers

Hi Addie;
15x2 + 11x - 56 = 0
 
Let's break this down...
15x2
(x)(x)=x2
(5)(3)=15 or (15)(1)=15
 
11x
11x=(11x+0x) or (10x+1x) or (9x+2x), etc
 
-56
(-8)(7) or (8)(-7)
 
Let's factor...
15x2 + 11x - 56 = 0
(?x+  ??)(?x-  ??)
 
Because the 11x is positive, the added ??x must be greater than the subtracted ??x.
(3x+7)(5x-8)=0
Let's FOIL...
FIRST.....15x2
OUTER...-24x
INNER.....35x
LAST.......56
 
15x2-24x+35x+56=0
15x2+11x-56=0
 
 
 
 
 
 

Comments

You are SOOOOO welcome.
Keep those questions coming.

Comment

I will show you a trick that solves all this kind of problems.
 
   15X+ 11X - 56 
 
    A quadratic like this can only be factorable, if  There exist 2 rational numbers whose Sum is 11, and 
   their product is  - 15 * 56
 
          So we rite 15 * 56  as product of its factor
  
            15 * 56 =  3 * 5 * 7 * 8 = 15 * 56 = 35 * 24 = 
 
                   Now we see that  the difference of 35 and 24 is 11
 
                15 X+ 35X - 24X -56   ( break up 11X into 35X- 24X)
                 
              5X( 3X +7 )  - 8 ( 3X + 7)  , Now 2 terms have common factor  of (3X +7 )
 
                ( 3X + 7 ) ( 5X - 8 )    This is the final answer.